1994
DOI: 10.1002/app.1994.070510212
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dissolution. I. On the dissolution behavior of copolymers of methyl methacrylate and methacrylic acid

Abstract: SYNOPSISCopolymers of methyl methacrylate with methacrylic acid [ P (MMA/MA) ] are interesting resist materials for microlithography. At moderate baking temperatures, these copolymers undergo an intramolecular cyclization, yielding terpolymers containing anhydride moieties. This process has striking consequences for the dissolution behavior and results in higher ketone solubilities. The dissolution rates in methyl ethyl ketone (MEK) and in mixtures with ethyl glycol (EG) correlate in an Arrhenius-like manner w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This material was synthesized by conventional radical polymerization of methyl methacrylate and methacrylic acid in refluxing tetrahydrofuran solvent using 2,2′-azobis(isobutyronitrile) as the initiator. 40 The polymer molecular weight Mw was 12 800 with a polydispersity of 1.83. Analysis of the polymer composition 41 by C-13 NMR showed that 18-21% of the polymer repeat units were methacrylic acid on a molar basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This material was synthesized by conventional radical polymerization of methyl methacrylate and methacrylic acid in refluxing tetrahydrofuran solvent using 2,2′-azobis(isobutyronitrile) as the initiator. 40 The polymer molecular weight Mw was 12 800 with a polydispersity of 1.83. Analysis of the polymer composition 41 by C-13 NMR showed that 18-21% of the polymer repeat units were methacrylic acid on a molar basis.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(methyl methacrylate- co -methacrylic acid) (P(MMA − MAA)) . This material was synthesized by conventional radical polymerization of methyl methacrylate and methacrylic acid in refluxing tetrahydrofuran solvent using 2,2‘-azobis(isobutyronitrile) as the initiator . The polymer molecular weight M w was 12 800 with a polydispersity of 1.83.…”
Section: Methodsmentioning
confidence: 99%
“…They proposed that these observations were due to the thermodynamic compatibility of the copolymers with MIBK and the T g of the copolymers. Reinhardt et al [28] also studied the dissolution of a PMMA copolymer, poly(methyl methacrylate-comethacrylic acid). These particular copolymers are interesting because at moderate baking temperatures, they undergo an intramolecular cyclization producing terpolymers containing anhydride moieties.…”
Section: Effect Of Polymer Structure Composition and Conformationmentioning
confidence: 99%